Making debate more inclusive for the student-veteran debater. (3rd April 2017) - Sciullo, Nick J.
ABSTRACT: The debate about debate's inclusiveness has been prominent in scholarship and debate rounds as well for many years. Yet one significant group has not been included in those discussions: military veterans who return to school after serving their country. I argue that we should welcome student-veterans into debate and propose several strategies for doing just that. Student-veterans have unique insights into many of debate's recurring discussions (war, arms trade, violence, aggression, etc.) that could benefit all debaters. If debate is to be the welcoming space many debaters and debate coaches have been working toward, then debaters and debate coaches must proactively work at inclusion of student-veterans in the activity. I support these arguments with a discussion of the historic National Debate Tournament run of Georgia State University's Floyd and Finch in 2014 in order to highlight the promises and pitfalls of welcoming student-veterans in the debate activity.